Anteroposterior Translational Malalignment of Ankle Arthrodesis Alters Foot Biomechanics in Cadaveric Gait Simulation. Issue 2 (8th October 2019) - Imsdahl, Sheri I.; Stender, Christina J.; Cook, Brian K.; Pangrazzi, Garett; Patthanacharoenphon, Cameron; Sangeorzan, Bruce J.; Ledoux, William R.
ABSTRACT: Tibiotalar arthrodesis is a common surgical treatment for end‐stage ankle arthritis. Proper ankle alignment is important as malalignment can lead to complications that may require revision surgery. This study aimed to determine how anteroposterior (AP) translational malalignment of ankle arthrodesis affects distal foot joint kinematics and plantar pressure. Ankle arthrodesis was performed on 10 cadaveric foot specimens using a custom fixture that could fuse the ankle neutrally and induce discrete malalignments (3, 6, and 9 mm) anteriorly and posteriorly. Gait was simulated under each alignment with a robotic gait simulator, and foot bone motion and plantar pressure were quantified. AP translational malalignment did not substantially affect plantar pressure or joint range of motion, but there were several significant differences in joint position throughout stance phase. Differences were seen in five joints (talocalcaneal, talonavicular, calcaneocuboid, fifth tarsometatarsal, and first metatarsophalangeal) and in the position of the first metatarsal relative to the talus. The most extreme effects occurred when the talus was displaced 6 mm or more posteriorly. In vivo, this may lead to aberrant joint loading, which could negatively impact patient outcomes. © 2019 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 38:450‐458, 2020